2023
DOI: 10.1101/2023.11.12.566704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved 5-methyluridine tRNA modification modulates ribosome translocation

Joshua D. Jones,
Monika K. Franco,
Mehmet Tardu
et al.

Abstract: While the centrality of post-transcriptional modifications to RNA biology has long been acknowledged, the function of the vast majority of modified sites remains to be discovered. Illustrative of this, there is not yet a discrete biological role assigned for one the most highly conserved modifications, 5-methyluridine at position 54 in tRNAs (m5U54). Here, we uncover contributions of m5U54 to both tRNA maturation and protein synthesis. Our mass spectrometry analyses demonstrate that cells lacking the enzyme th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“… Modification circuits involving tRNA core modifications: ( a ) modification circuits identified in T. thermophilus in response to temperature changes represented on a cloverleaf scheme [ 94 , 95 , 107 ]; ( b ) T-arm modification circuits identified in yeast [ 69 , 70 ]; ( c , d ) modification circuits identified in E. coli [ 109 , 110 , 111 ]; and ( e ) modification circuits identified in E. coli [ 111 ]. Modifications are represented by colored circles (see the legend in the box for the corresponding colors).…”
Section: Influence Of Trna Core Modification On Trna Structure and St...mentioning
confidence: 99%
See 4 more Smart Citations
“… Modification circuits involving tRNA core modifications: ( a ) modification circuits identified in T. thermophilus in response to temperature changes represented on a cloverleaf scheme [ 94 , 95 , 107 ]; ( b ) T-arm modification circuits identified in yeast [ 69 , 70 ]; ( c , d ) modification circuits identified in E. coli [ 109 , 110 , 111 ]; and ( e ) modification circuits identified in E. coli [ 111 ]. Modifications are represented by colored circles (see the legend in the box for the corresponding colors).…”
Section: Influence Of Trna Core Modification On Trna Structure and St...mentioning
confidence: 99%
“…Recently, several reports have shed light on modification cross-talks among tRNA core modifications in E. coli . They reported that the introduction of U47 is globally enhanced by the prior presence of m 7 G46 [ 109 ] and also stimulated by m 5 U54 in E. coli , , , and [ 110 , 111 ] ( Figure 3 c). 55 seems to also participate in this network, in which it may either slightly stimulate or inhibit the introduction of U47 in E. coli and , respectively [ 111 ].…”
Section: Influence Of Trna Core Modification On Trna Structure and St...mentioning
confidence: 99%
See 3 more Smart Citations